The state of phisical development and annual changes in selected morphological functional characteristics in school-girls of the textil industry GZPJ works school in Gorzów Wielkopolski - Tuszyński, Krzysztof; Bzdega-Sobocinska, Lidia; Kopaczyk, Franciszek (Anthropological Review, 1976)
The aim of this work is to characterise the physical development of a girls’ group — pupils of the textile industry at the Silk Industry Works „Silvana” in Gorzów Wielkopolski, training for the profession of weather. The material for this research consisted of 40 pupils, who were tested in 1972 at the age of 17 and then in 1973 at the age of 18. The results of those researches are given in Table 1.